PELATIHAN PROFESIONALISME PADA TENAGA MITRA KERJA (TMK) PT. PERSONEL ALIH DAYA (PERSADA) MAKASSAR - Siti Azizah Dalauleng, Andi; Rezky Ramadhani, Devita; Rahmat, Abdul (JOURNAL OF COMMUNITY DEDICATION, 2022)
Training is a forum for companies to build capable human resources towards a globalization era which is full of competition and challenges. Bariqi (2018) describes several objectives and benefits of training, namely for productivity, quality, workforce planning, morale improvement, indirect compensation, occupational safety and health, prevention of expiration, and personal development. The preparation of this training program has two stages, namely determining the theme of the training and compiling training modules based on the problems that have been determined. The results of this training showed that there were 75% or 27 participants who experienced an increase in knowledge, and 25% or 9 participants who did not experience an increase in knowledge. Based on these results, it can be concluded that there is an increase in knowledge as measured through the pretest and posttest of 50% + 1 participant, so that the training carried out affects the level of understanding of participants regarding professionalism in work.